Adenoid Cystic Carcinoma of Lung: A Case Report - Coşkun, Feyza; Çekirdekçi, Ahmet; Yekeler, Hayreddin; Muz, M. Hamdi; Çobanoğlu, Bengü (Fırat University, 2003)
Adenoid cystic carcinomas of lung are very rare carcinomas which are seen arroximataly 0.2% in general population. These carcinomas are typically slow growing, usually centrally located and have long survival rates. Surgical resection and adjuvant radiotherapy is the choise of treatment. The case of 50 years old female patient who had right flank pain and sputum in the mornings for 10 years and took the diagnosis of pulmonary adenoid cystic carcinoma, was reported due to the rarely of the disease.

Akciğerin adenoid kistik karsinomları, oldukça ender olup yaklaşık olarak %0.2 oranında görülmektedir. Tipik olarak yavaş büyüyen, çoğunlukla santral yerleşimli ve uzun sağkalım ile birlikte olan tümörlerdir. Tedavide cerrahi rezeksiyon ve adjuvan radyoterapi önerilmektedir. 10 yıldır sağ yan ağrısı ve özellikle sabahları bol balgam çıkarma öyküsü olan 50 yaşındaki bayan hastanın akciğerinde saptadığımız adenoid kistik karsinom ender görülmesi nedeniyle sunuldu.
Akciğerde Adenoid Kistik Karsinoma: Olgu Sunumu